Consumer Credit as a Provision of General Interest? - Irina Domurath (Wirtschaftsdienst)
Abstract The COVID-19 pandemic has shown once again that it is often the poor who suffer from economic downturn in times of crisis. As was the case in the financial crisis of 2008, we now have an opportunity to rethink the role of consumer credit in society and design and create a legal framework that adequately reflects that role. The following thought experiment hopes to give impetus to legal reforms.